Me Time Dalam Ayunan TRADISI BAAYUN ANAK SUKU BANJAR - Indrayani, Rusmiati (Ekonomi Syariah STAI Sangatta Kutai Timur, 2020)
The aim of this study was to describe the function of Baayun tradition on child psychology. The method used was descriptive qualitative with ethnographic approach to studying the Banjar ethnic with a natural setting. The focus of cultural research tends to be phenomenological. The roles and functions of individual and social culture are related to the mindset, behavior and traditions of surviving societies as well as cultural efforts in maintaining their lives. All existing realities are understood naturally as they are, so that phenomenological understanding of the symptoms of tradition focuses on the reciprocal relationship between the functions of the children's beyond tradition and the life (culture) of Banjar Tribe substantively.The results showed that there was three traditional functions of child psychology, including; (1) The function of the directive as a tool to instil disciplinary character values and to obey the rules of sleeping hours for their benefit; (2) The informative function, namely the educational space in the cognitive realm that contains religious knowledge, such as regarding the attributes of Allah and the knowledge of the Prophet's morals. Information on faith education and akhlakul karma is conveyed by parents by singing a lullaby called bakery;3) Affective function is the most important function for the child's psyche. In adulthood, the security and cherished feelings that reside in the memory provided.